Can We Cryopreserve the Sperm of COVID-19 Patients During the Pandemic? - Wu, Yongming; Zhang, Xiaoxue; Wang, Zhiqiang; Xia, Xinyi (Frontiers in Endocrinology, 2022)
Abstract: An extreme strain has been placed on healthcare facilities in the COVID-19 era. Initial stage of the pandemic, national and international societies for reproductive medicine suggested the suspension of new IVF treatments and non-essential cryopreservation of gametes. Accordingly, the demands of cryopreservation of semen with COVID-19 patients also was suspended by some of cryobanks to protect staff and patients from unnecessary viral exposure at the acute stage. However, the pandemic may stay with us longer than expected. In addition, there will be some male COVID-19 patients with cancer or critically illness who needs to cryopreserve their semen before medical treatments, otherwise they might loss the chance of getting their own offspring. In this document, we summarize available evidence to deepen and expand awareness of feasibility of sperm cryopreservation and propose some suggestions to help cryobanks carry out sperm preservation procedure for COVID-19 male patients.